Development of the E-module with Project-Based Learning for the Flat Pattern Design Course - Pepi Resmanti; Anni Faridah; Yusmerita Yusmerita; Yeka Hendriyani (Yayasan Keluarga Guru Mandiri, 2024)
This research was motivated by the disappointing results of student projects and the perceived lack of engagement with current instructional materials in flat pattern design courses. The aim was to create a project-based learning e-module designed specifically for this field of study. The study followed Borg and Gall's (1989) research and development (RD) model. Participants consisted of three lecturers and 36 students. Data collection involved using questionnaires and evaluating student project outcomes. The results suggest that the project-based learning e-module is effective and practical in flat pattern design education, promising to improve student learning outcomes. The lecturer responses indicated a 91% rating in the